Care of the dying, dead, and bereaved: developing the curriculum framework in undergraduate nursing education - Agustina, Hana Rizmadewi (2021)
There is a lack of research in undergraduate nursing in end of life support and death in the Indonesian context. End of life care is less emphasised both in the pre-clinical and clinical training stages within the Indonesian curriculum compared to western countries. This study aims to develop an empirical and theory-driven curriculum framework for undergraduate nursing students in Indonesia focused on the care of the dying, dead, and bereaved.